The role of joints of lower limb during shock absorbing phase in race walking - lto, Y.; Yamamoto, K. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the role of each joint of the lower limb during the shock absorbing phase in race walking (RW) by comparing it with normal walking (NW) and running (RU). Three active race walkers participated in this study. They performed NW, RW and RU (toe-strike) with self-selected speed in a motion capture laboratory. An optical 3D motion capturing system with two force plates was used. The vertical fluctuation of the center of mass in RW was the smallest among the three movements. The negative power at the ankle and knee joint were hardly detected in RW, however, a relatively large negative power was observed at the hip joint. The negative works of both total and individual joint were obtained by integrating the negative power during the shock absorbing phase. The total negative work in NW (0.14 Wlkg) was the smallest among the three motions. The ratio of the hip joint was greater (36.7%) than the other joints in RW.